Patch antenna sensor rosettes for surface strain measurement. Issue 2 (18th July 2017) - Li, Dan; Cho, Chunhee; Wang, Yang
Abstract : Passive (battery-free) wireless patch antenna sensors have been developed in recent years for strain sensing, to provide convenient and low-cost instrumentation. Despite past efforts, current analytical and experimental studies have mainly focused on performance in single-axial measurement, which is simple and unrealistic from typically encountered arbitrary plane stress fields. This paper presents strain sensor rosettes made of folded patch antennas and slotted patch antennas for measuring an arbitrary surface strain (plane stress) field. The transverse strain effect of both sensors is discussed and has been validated through laboratory experiments. Multiphysics coupled simulation is conducted to describe accurately the mechanical and electromagnetic behaviours of antenna sensors. Resonance frequency shifts of the antenna sensors are used to derive the three strain components in an arbitrary plane stress scenario – that is, two normal and one shear strain components. Both numerical studies and experimental validations have been performed.